2003
DOI: 10.1101/gad.1093903
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Mcl-1 is required for the initiation of apoptosis following ultraviolet irradiation

Abstract: Ultraviolet (UV) irradiation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
593
5
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(651 citation statements)
references
References 49 publications
(38 reference statements)
51
593
5
2
Order By: Relevance
“…22 Pro-apoptotic functions of the proteasome have been described in several instances including the constitutive death of neutrophils as well as NGF withdrawal, DNA damage, glucocorticoid treatment and reduced extracellular potassium. [23][24][25][26][27] Additionally, the proteasome has been implicated in the early stages of wallerian degeneration after axotomy. 28 In response to DNA damage, the large Bcl-2 homology domain-only protein Mule/ARF-BP1 was shown to ubiquitylate Mcl-1 -an anti-apoptotic Bcl-2 family member -thereby causing its degradation via the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…22 Pro-apoptotic functions of the proteasome have been described in several instances including the constitutive death of neutrophils as well as NGF withdrawal, DNA damage, glucocorticoid treatment and reduced extracellular potassium. [23][24][25][26][27] Additionally, the proteasome has been implicated in the early stages of wallerian degeneration after axotomy. 28 In response to DNA damage, the large Bcl-2 homology domain-only protein Mule/ARF-BP1 was shown to ubiquitylate Mcl-1 -an anti-apoptotic Bcl-2 family member -thereby causing its degradation via the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…16 In contrast, Green and colleagues suggest a growth factor-dependent regulation of MCL-1 stability. 23 Perhaps, the difference in cell types lie at the heart of this discrepancy; in growth factor-dependent cell lines, the regulation of MCL-1 levels may be under a different level of control than in fibroblasts.…”
Section: How Does Phosphorylation Regulate Mcl-1 Degradation?mentioning
confidence: 97%
“…16 Wang and colleagues have demonstrated that in response to genotoxic stress the proteasome-dependent elimination of MCL-1 is required for downstream apoptotic events including BAX and BAK oligomerization, cytochrome c release, and caspase activation. Treatment of cells with proteasome inhibitors could block the elimination of MCL-1 and prolong survival.…”
Section: Regulation Of Mcl-1 Half-lifementioning
confidence: 99%
See 1 more Smart Citation
“…MCL-1 protein is unique among antiapoptotic BCL-2 family members in that it has a short half-life and is the target of the ubiquitin/proteasome-dependent degradation pathway. 42 This degradation may be regulated by cytokines as growth factor withdrawal resulted in MCL-1 phosphorylation by glycogen synthase kinase-3b and enhanced ubiquitinylation. 43 These data suggest that during lymphocyte development, MCL-1 phosphorylation may play a critical role in regulating its protective function and expression, but this hypothesis still needs to be tested in vivo.…”
Section: Cytokines Regulate Survival In Early Lymphocyte Developmentmentioning
confidence: 99%